Foreign experience of entrepreneurship infrastructural support - U. G. Tribunskaya (Путеводитель предпринимателя)
The article describes the experience of support and development of small and medium enterprises in foreign countries. Business in Russia is at the initial stages of development, in this regard needs to be supported. The analysis of the experience of foreign countries, which proved its efficiency in practice, will consider the possibility of applying some of their instruments of support in Russia.